Perspectives on diet and physical activity among urban African Americans with serious mental illness. (28th May 2019) - Sayer, Janis; Paniagua, Deysi; Ballentine, Sonya; Sheehan, Lindsay; Carson, Margaret; Nieweglowski, Katherine; Corrigan, Patrick; ,
ABSTRACT: African Americans are burdened by high rates of obesity that contribute to chronic disease and early mortality. To tailor a weight loss intervention to meet the needs of African Americans with serious mental illness, a community-based participatory research (CBPR) team comprised primarily of African Americans with serious mental illness guided qualitative research to understand factors that affect weight and interventions that may diminish obesity. Data from five focus groups (n = 55) were analyzed to better understand this group's needs. Participants voiced individual, social, and structural barriers to maintaining and achieving a healthy weight and provided perspectives on potential solutions.